Metabolic rate and insulin-independent glucose uptake increase in a TDP-43Q331K mouse model of amyotrophic lateral sclerosis - Tanya S. McDonald; Cedric S. Cui; Titaya Lerskiatiphanich; Jianina Marallag; John D. Lee (Heliyon)
Impaired glucose regulation is increasingly recognised in amyotrophic lateral sclerosis (ALS), yet the precise mechanisms remain unclear. Here, we investigated energy balance and glucose control in TAR DNA-binding protein 43 (TDP-43)Q331K mice, a model of ALS, at both the early and late symptomatic stages of disease. Mutant TDP-43Q331K mice and non-transgenic controls underwent indirect calorimetry, as well as intraperitoneal glucose, insulin, and glucagon tolerance testing. We also examined plasma hormone levels and quantified α- and β-cell areas in pancreatic islets. Throughout disease progression, TDP-43Q331K mice exhibited elevated metabolic rates, with a transient increase in food intake at the early stages. At the later stages of disease, heightened glucose uptake was observed despite unchanged insulin secretion or tolerance, indicating mechanisms independent of insulin. Notably, TDP-43Q331K mice maintained fasting blood glucose levels even when circulating glucagon levels were reduced, suggesting that alternative pathways contribute to preserving euglycemia. These findings reveal a distinct metabolic profile in TDP-43Q331K mice, underscoring the complexity of glucose dyshomeostasis in ALS.